2020
DOI: 10.1097/qad.0000000000002785
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I mimetics attenuate macrophage activation in chronic treated HIV

Abstract: Objective(s): Despite antiretroviral therapy (ART), there is an unmet need for therapies to mitigate immune activation in HIV infection. The goal of this study is to determine whether the apoA-I mimetics 6F and 4F attenuate macrophage activation in chronic HIV. Design: Preclinical assessment of the in-vivo impact of Tg6F and the ex-vivo impact of apoA-I mimetics on biomarkers of immune activation and gut barrier dysfunction in treated HIV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(75 citation statements)
references
References 45 publications
4
71
0
Order By: Relevance
“…Mu et al (93) recently reported that in humanized mouse models of HIV that were maintained on a chow diet and treated with antiretroviral therapy to suppress plasma HIV to below detectable levels, there was evidence of gut barrier dysfunction and increased levels of LPS in plasma, which were ameliorated by adding Tg6F (but not the EV control) to the mouse chow. Mu et al (93) did not investigate intestinal mucus, they did not measure oxidized phospholipids or ROS, but they did find increased levels of oxidized lipoproteins in gut tissue in these chow-fed mice that was reduced by the addition of Tg6F.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mu et al (93) recently reported that in humanized mouse models of HIV that were maintained on a chow diet and treated with antiretroviral therapy to suppress plasma HIV to below detectable levels, there was evidence of gut barrier dysfunction and increased levels of LPS in plasma, which were ameliorated by adding Tg6F (but not the EV control) to the mouse chow. Mu et al (93) did not investigate intestinal mucus, they did not measure oxidized phospholipids or ROS, but they did find increased levels of oxidized lipoproteins in gut tissue in these chow-fed mice that was reduced by the addition of Tg6F.…”
Section: Discussionmentioning
confidence: 99%
“…Mu et al (93) recently reported that in humanized mouse models of HIV that were maintained on a chow diet and treated with antiretroviral therapy to suppress plasma HIV to below detectable levels, there was evidence of gut barrier dysfunction and increased levels of LPS in plasma, which were ameliorated by adding Tg6F (but not the EV control) to the mouse chow. Mu et al (93) did not investigate intestinal mucus, they did not measure oxidized phospholipids or ROS, but they did find increased levels of oxidized lipoproteins in gut tissue in these chow-fed mice that was reduced by the addition of Tg6F. Based on the data presented here, we think that the addition of Tg6F in the studies of Mu et al (93) may well have prevented an increase in oxidized phospholipids, ROS and LPS in jejunum mucus that was responsible for their observed increase in gut permeability and increased plasma LPS levels (93).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To bypass limitations of preclinical animal models of chronic treated HIV, we recently described a robust translational preclinical approach, where we used both NOD.Cg-Prkdc scid Il2rg tm1Wjl /SzJ (NSG) and Graft versus host disease (GVHD)-resistant C57BL/6 recombination activating gene 2 (Rag2)γcCD47 triple knockout (TKO) BLT mice [18][19][20][21][22][23] on independent ART regimens and gut explants from HIV infected participants to demonstrate that apoA-I mimetics attenuate innate immune activation, gut barrier dysfunction, plasma and intestinal oxidized lipoproteins in chronic treated HIV [24]. Herein, using murine biospecimens (blood and gut tissues) and human biospecimens (gut tissues) from our recently published study [24], we demonstrate that apoA-I mimetics consistently reduce plasma and gut tissue cytokines (TNF-α, IL-6) and chemokines (CX3CL1) and gut protein levels of the chemokine receptor CX3CR1. ApoA-I mimetics also reduced gut protein levels of the A disintegrin and metalloprotease 17 (ADAM17), an inflammation-inducible enzyme that is responsible for the protease-driven shedding of TNF-α, CX3CL1 and sCD163 [25], one of the most robust biomarkers of innate immune activation that is strongly associated with mortality in chronic treated HIV [9].…”
Section: Introductionmentioning
confidence: 99%
“…One of these peptides named 6F that is expressed as a transgene in tomatoes, when concentrated (Tg6F) and administered orally, works mainly in the gut to inhibit gut inflammation and progression of inflammatory diseases in mice [11,13,14]. In this report, by using a previously described validated translational approach with independent humanized mouse models of chronic treated HIV and human gut explants from HIV infected persons that showed that that the apoA-I mimetic peptides 4F and 6F attenuate biomarkers of immune activation [15], we also demonstrate that apoA-I mimetics attenuate increased blood and gut bioactive lipids and intestinal COX-2 in chronic treated HIV. Our data provide proof of concept that apoA-I mimetic peptides may be a novel therapeutic strategy to target intestinal COX-2 and bioactive lipids as instigators of inflammation, gut barrier dysfunction and cardiometabolic syndrome in chronic treated HIV.…”
Section: Introductionmentioning
confidence: 92%